III. Personal papers of Thomas MacDonagh, - MacDonagh, Thomas, 1878-1916 (1903)
Personal papers of Thomas MacDonagh, including a notebook dated 1903, assorted financial papers (lodgement slips and a cheque book), correspondence and documentation relating to his teaching post in the National University and his will. Also included is a Christmas card, bearing MacDonagh's portrait, issued by President Sean T. Ó Ceallaigh (1950).